Study of grinding and polishing tools in automated processing of curved stone - Yun Shen; Jing Lu; Changcai Cui (Case Studies in Construction Materials, 2022)
The grinding and polishing of curved stone involve many steps, limiting the process's efficiency. This study proposes a one-step grinding and polishing process to simplify the process and achieve efficient machining. It is achieved by developing the grinding and polishing tools and realizing the entire process on the robotic processing platform, and the tool design is based on the surface roughness of the machined workpiece. The grinding tool is made by selecting the appropriate glue to achieve the connection from carving to polishing. Similarly, the polishing tool is made by selecting the appropriate gel compound system to achieve a high glossiness curved stone surface. The results show that the grinding tool made of epoxy resin YT-CC301 can reduce the curved stone's roughness from 16.281 µm to below 400 nm, and the connection from carving to polishing can be realized by one step. The polishing tool made of sodium alginate and carboxylated chitosan gel compound system or sodium alginate and sodium carboxymethyl cellulose gel compound system can polish the surface of the ground curved stone to the roughness of less than 15 nm, and the surface glossiness can reach more than 120. Therefore, a single step of grinding and polishing of curved stone is achieved.